1996
DOI: 10.1073/pnas.93.10.5131
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial diversity and the origins of African and European cattle.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
427
2
9

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(469 citation statements)
references
References 22 publications
31
427
2
9
Order By: Relevance
“…Because of this variability, the control region has frequently been used to estimate population divergence and gene flow (e.g., reviewed by Hoelzel 1994), effective population size (Rooney et al 2001;Roman and Palumbi 2003), and population expansion or decline (e.g., Bradley et al 1996) in natural populations. However, in many organisms such as primates and rodents, several features of the control region complicate genealogical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this variability, the control region has frequently been used to estimate population divergence and gene flow (e.g., reviewed by Hoelzel 1994), effective population size (Rooney et al 2001;Roman and Palumbi 2003), and population expansion or decline (e.g., Bradley et al 1996) in natural populations. However, in many organisms such as primates and rodents, several features of the control region complicate genealogical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, introgression of Indian zebu bulls (Bos indicus) in taurine herds occurs and has improved the tolerance of the cattle (Bos taurus) to hot and dry environments (Epstein, 1971;Bradley et al, 1994Bradley et al, , 1996Loftus et al, 1994b;Frisch et al, 1997;Hanotte et al, 2000). Bongso et al (1988) described a spontaneous hybridization of wild gaur and zebu.…”
Section: Introductionmentioning
confidence: 99%
“…These data do not support the recent hypothesis on the origin of Y1 from the local European hybridization of cattle with male aurochsen. Compared with mtDNA, the intensive culling of breeding males and male-mediated crossbreeding of locally raised native breeds has accelerated loss of Ychromosomal variation in domestic cattle, and affected theIntroduction Analyses of mitochondrial DNA (mtDNA) D-loop sequences and Y-chromosome-specific polymorphisms (such as single nucleotide polymorphisms, insertiondeletion mutations and microsatellites) have indicated that humpless taurine (Bos taurus) and humped zebu cattle (B. indicus) have clearly distinguishable mtDNA and Y-chromosomal haplotypic profiles Bradley et al, 1996;Hanotte et al, 1997;Mannen et al, 2004;Götherström et al, 2005;Li et al, 2007b). This observation points towards two independent domestication events from genetically differentiated aurochs (B. primigenius) populations for the two basic taxa of domestic cattle.…”
mentioning
confidence: 99%
“…Our current knowledge of mtDNA variation of taurine cattle in Eurasia is based on studies of European and Near Eastern breeds Bradley et al, 1996;Troy et al, 2001). In recent years, a few East Asian breeds have also been examined (Mannen et al, 2004;Lai et al, 2006).…”
mentioning
confidence: 99%